The Jurisprudential Controls Related to the Contract of Dhimmi - Al-Qatabri, Khalid Mohammad (Dirasat: Shari'a and Law Sciences, 2020)
In this research, the researcher tries to feel the justice of Islam and its permissibility through dealing with non-Muslims, especially the people of the Dhimha, especially after the enemies of Islam emerged, whether they call themselves Muslims or others and attributed the abuse of these to Islamic legislation through the application of Muslims. The research was divided into sections. The most important of which was the definition of the most important terms, namely the concept of the officer, jurisprudence, contract and dhimmi. Also, the most important element in the contract of dhimma, which is between him and the authority of the conclusion of the contract of dhimmi on the one hand and on the other with the identification of the categories that are held to clarify the relationship between Muslims and people of dhimma. The study found that the dhimmi contract is for all Kuffaar except Arab idol worshippers. The call to the religion of Allah is the origin of the relationship between Muslims and other non-Muslim nations. The study used the inductive approach by tracing the Fiqh books adopted in the four madhhabs. As well as the deductive approach by extracting the Fiqh controls related to the dhimma contract. The study recommended the importance of conducting more research on the Fiqh controls related to the rulings of dhimmis and the need to clarify the Fiqh of the treatment of non-Muslims by mentioning the gift of the Prophet (peace and blessings of Allaah be upon him) in his treatment of non-Muslims.